Proximate composition, amino acids and fatty acids profiles of wild and cultured Climbing Perch, Anabas testudineus (Bloch, 1795) (Bangladesh Journal of Zoology, 2021)
The availability and compositions of foods in the aquatic system have a direct influence on nutritional compositions of fish muscle. This research aimed to determine the nutritional compositions of wild and cultured climbing perch, Anabas testudineus, between pre-monsoon and post-monsoon. The proximate compositions, total amino acid, and fatty acid profiles were determined by AOAC, HPLC and GC, respectively. The results in dicated that proximate (e.g., moisture, ash, protein and lipid), amino acid and fatty acid profile varied significantly (p